Islamic Ethics and Intrinsic Value of Human Being - عبدالرزاق حسامی فر (Journal of Philosophical Investigations, 2012)
One of the most important debates in Islamic ethics is the place of humanethics and its priority or posteriority in relation to the jurisprudence which deals with acts of worship. Given the diverse approaches towards Islam, there are different ideas on thisproblem. Some Muslims overlook human principles in the name of religion in their approach to Islam. Some others try to interpret Islam in such a way as not to contradict the principles of human ethics. In spite of some Muslim scholars’ view on the priority of jurisprudence over the ethics, this articleis a try, by appealing to certain Islamic evidence, atshowing thepriorityof ethicsover the jurisprudence and insisting on the importance and even the dominance of human ethics and intrinsic value of human beingin Islamic ethics. And it will conclude that according to the Islamic teachings, one can eitherhavehuman dignity and at the same time not bea Muslim,or bea Muslimand at the same time lack human dignity. So, neithersuperficial Islam necessarily leads tohonor nor does not being a Muslim repudiate honor, and what is emphasized in Islam is that human dignity is included in Islam and a real Muslim tries to earn it.